Perbedaan Lama Waktu Fermentasi Pakan Komersial yang Ditambahkan Boster Aquaenzym dan Em4 pada Pertumbuhan Ikan Betok (Anabas testudineus) - Firda Yanti; Rustiana Widaryati (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
This study aims to determine the effect of fermentation time with the addition of Boster Aquaenzym and EM-4 in commercial feed to increase growth and efficiency of feed utilization of Papuyu fish (Anabas testudineus) and to determine the right time to increase growth and efficiency of Papuyu fish (Anabas testudineus. The method used is carried out by fermenting commercial feed for different lengths of time, namely treatment A for 3 days, treatment B for 5 days and treatment C for 7 days. The results of this study showed that commercial fermented feed had the highest value in treatment C for 7 days with the highest value of weight growth. in treatment C (7,63) and feed utilization efficiency with the highest value in treatment C (95,91%). The addition of Boster Aquaenzym and EM-4 in fermented commercial feed proved to be good for growth and good feed quality. Keywords : Booster Aquaenzym, Papuyu Fish (Anabas testudineus), feed efficiency, survival, water quality